Patella Eversion Reduces Early Knee Range of Motion and Muscle Torque Recovery after Total Knee Arthroplasty: Comparison between Minimally Invasive Total Knee Arthroplasty and Conventional Total Knee Arthroplasty. (6th December 2010) - Majima, Tokifumi; Nishiike, Osamu; Sawaguchi, Naohiro; Susuda, Kouichi; Minami, Akio
Abstract : We hypothesized that patella eversion during total knee arthroplasty (TKA) reduces early return of active knee extension and flexion, quadriceps muscle strength, and postoperative pain. In 100 conventional TKA knees and 100 minimally invasive TKA (MIS TKA) knees, we compared knee range of motion (ROM), postoperative pain, and quadriceps muscle strength at 1 day, 4 days, 1 week, 2 weeks, 3 weeks, 4 weeks, 12 weeks, 1 year, and 5 years after surgery. The differences of surgical approach between MIS TKA and conventional TKA of this study are length of skin incision with subcutaneal flap and patella eversion. In MIS TKA, skin incision is shorter than conventional TKA. Furthermore, patella is not everted in MIS TKA procedure. There were no significant differences in preoperative factors. Postoperative improvement of ROM, postoperative muscle strength recovery, and postoperative improvement of visual analog scale were faster in patients with MIS TKA when compared to that in patients with conventional TKA. On the other hand, no significant difference was observed in complication, 5-year clinical results of subjective knee function score, and the postoperative component angle and lower leg alignment. These results indicate that patella eversion may affect muscle strength recovery and postoperative pain.